Analisis Kinerja Inkubator Bisnis Dalam Pendampingan Usaha Tenant - Agus Dwi Atmoko (Politeknik Sawunggalih Aji, 2021)
Presidential Regulation No. 27 of 2013 on Small Business Incubator Development define an incubator business as an institution that gives their business assistance to their tenants. The aims of this research is to assess perfomance of business and technology incubator in mentoring business tenant. The research was held in business and technology incubator of Politeknik Sawunggalih Aji and done by interviewing manager and tenants incubator. The type of research used is a quantitative descriptive. The source obtained was analyzed by a method balanced scorecard (BSC). The research finding show, the score of performance achievement of